Determinants of vitreomacular traction width: associations with foveal floor width and vitreoretinal interface changes. Issue 5 (16th November 2020) - Grinton, Michael; Melville, Harry; George, Grace; Tyagi, Pallavi; Avery, Peter; Wickham, Louisa; Steel, David H.
Abstract: To investigate the relationship between vitreomacular traction (VMT) width, foveal floor width (FFW) and other anatomical characteristics between eyes of patients with VMT. Retrospective observational study of unilateral and bilateral VMT cases from two specialist ophthalmic centres in the United Kingdom (UK) between 2016 and 2018. For unilateral VMT cases: VMT width in the affected eye and FFW in the non‐affected fellow eye were measured. In bilateral VMT cases: VMT width in both eyes was measured. In all cases, the presence of any associated inner or outer retinal, and vitreoretinal interface (VRI) changes, including epiretinal membrane, was also documented. 88 patients fulfilled the study criteria: 57 having unilateral and 31 bilateral VMT. For unilateral VMT cases, log (VMT) width was significantly correlated with FFW ( r  = 0.347, p = 0.008). Using stepwise linear regression, FFW (p = 0.004) and VRI changes (p = 0.03) were both significantly associated with VMT width with a R 2 of 0.21. In bilateral VMT cases, there was strong positive correlation between log (VMT) width ( r  = 0.88, p < 0.001), and the presence of any VRI ( r  = 0.90, p < 0.001) or outer retinal changes ( r  = 0.50, p < 0.001) between the two eyes. These findings suggest that individual variations in foveal morphology as measured by the FFW, along with the presence of vitreoretinal interface changes, are associated with the extent of VMT width. VMT width, VRI and outer retinal changes were also highly correlated between eyes in bilateral VMT, suggesting that individual patient factors, which may be genetic or acquired, determine their presence and extent.